BARRIERS AND ENABLERS OF A REPORTING CULTURE: A SYSTEMATIC REVIEW OF PATIENT SAFETY INCIDENT REPORTING BY HOSPITAL HEALTHCARE WORKERS - Cyrilla Ayu Pamela; Trihaningsih Puji Astuti; Vira Amelia (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Patient safety incidents remain common in hospitals and directly affect the quality of healthcare services. Incident reporting is a key strategy for improving service quality and promoting a safety culture. An effective reporting culture requires the reduction of barriers and the strengthening of enabling factors so that healthcare workers feel safe to report incidents. Purpose: This systematic review aimed to identify barriers and supportive factors affecting the establishment of a patient safety incident reporting culture among healthcare personnel within hospital environments. Methods: A systematic review was undertaken through a comprehensive search of four databases, including ScienceDirect, ProQuest, PubMed, and. Google Scholar. The search terms were: ("patient safety" OR "adverse event") AND ("incident reporting" OR "error reporting") AND ("barriers" OR "enablers") AND ("healthcare workers") AND ("hospital" OR "healthcare"). Inclusion criteria were articles published from 2021 to 2026 and written in English, available as free full text and were selected tobe analyzed and assessed using JBI. A total of 619 records were initially identified. Following the removal of duplicates, screening of titles and abstracts, and full-text assessment according to the eligibility criteria, 15 studies were ultimately included in the review. The selection process followed PRISMA guidelines. Results: Common barriers to concerns about blame or punitive consequences, insufficient feedback, and complex reporting mechanisms. Enabling factors included leadership support, implementation of a non-punitive (just) culture, simple and anonymous reporting systems, regular training, and transparent feedback mechanisms. Conclusion: Patient safety incident reporting culture is influenced by individual, organizational, and system-related factors. Sustainable improvement requires strong leadership, non-punitive policies, simplified reporting processes, continuous training, and structured feedback systems.